Australian and New Zealand Pulmonary Rehabilitation Guidelines. Issue 4 (24th March 2017) - Alison, Jennifer A.; McKeough, Zoe J.; Johnston, Kylie; McNamara, Renae J.; Spencer, Lissa M.; Jenkins, Sue C.; Hill, Catherine J.; McDonald, Vanessa M.; Frith, Peter; Cafarella, Paul; Brooke, Michelle; Cameron‐Tucker, Helen L.; et al.
ABSTRACT: Background and objective: The aim of the Pulmonary Rehabilitation Guidelines (Guidelines) is to provide evidence‐based recommendations for the practice of pulmonary rehabilitation (PR) specific to Australian and New Zealand healthcare contexts. Methods: The Guideline methodology adhered to the Appraisal of Guidelines for Research and Evaluation (AGREE) II criteria. Nine key questions were constructed in accordance with the PICO (Population, Intervention, Comparator, Outcome) format and reviewed by a COPD consumer group for appropriateness. Systematic reviews were undertaken for each question and recommendations made with the strength of each recommendation based on the GRADE (Gradings of Recommendations, Assessment, Development and Evaluation) criteria. The Guidelines were externally reviewed by a panel of experts. Results: The Guideline panel recommended that patients with mild‐to‐severe COPD should undergo PR to improve quality of life and exercise capacity and to reduce hospital admissions; that PR could be offered in hospital gyms, community centres or at home and could be provided irrespective of the availability of a structured education programme; that PR should be offered to patients with bronchiectasis, interstitial lung disease and pulmonary hypertension, with the latter in specialized centres. The Guideline panel was unable to make recommendations relating to PR programme length beyond 8 weeks, the optimal model for maintenance after PR, or the use of supplemental oxygen during exercise training. The strength of each recommendation and the quality of the evidence are presented in the summary. Conclusion: The Australian and New Zealand Pulmonary Rehabilitation Guidelines present an evaluation of the evidence for nine PICO questions, with recommendations to provide guidance for clinicians and policymakers. Abstract : See article, page 622